2014
DOI: 10.1111/jwas.12092
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Anomalies of Pacu, Piaractus mesopotamicus, Larvae from a Wild‐caught Broodstock

Abstract: Skeletal anomalies in fish are frequent, representing a major problem for the aquaculture industry. The anomalies usually arise in the larval phase and worsen, persist, or recover over the ensuing stages of development. In addition to impairing larval quality, they compromise the growth, health, and food conversion of fish, lowering their economic value. This study evaluated the occurrence of skeletal anomalies in pacu larvae during the first 30 d of development. The newly hatched larvae of six breeding pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The aforementioned anomalies were also found in larvae deriving from wild broodstocks, as verified by Lopes et al. () in pacu Piaractus mesopotamicus , a phylogenetically closely related species of tambaqui. In this case, the appearance of anomalies is unpredictable, as several factors are involved in fish ontogeny.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The aforementioned anomalies were also found in larvae deriving from wild broodstocks, as verified by Lopes et al. () in pacu Piaractus mesopotamicus , a phylogenetically closely related species of tambaqui. In this case, the appearance of anomalies is unpredictable, as several factors are involved in fish ontogeny.…”
Section: Discussionsupporting
confidence: 60%
“…Tambaqui larvae will not develop its skeleton in a normal way when facing climate change expected for the end of the century, especially under moderate and extreme conditions of high temperatures, dissolved CO 2 and water acidity, as observed in the A1B and A2 scenarios (IPCC, ). These climatic conditions resulted in severely structurally compromised skeletons, with marked notochord curvatures (lordosis, scoliosis and kyphosis), certainly affecting the animal's welfare and its fitness both in natural and artificial environments (Boglione et al., , ; Izquierdo et al., ; Lopes, Freitas, Jomori, Carneiro, & Portella, ). Poorly developed structures in the craniofacial skeleton were also observed (e.g., crooked upper and lower jaws), which may hinder larvae growth by directly affecting food capture (Boglione et al., ), as verified in the A2 scenario.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with the results of LOPES et al (2014) who reported absence of skeletal abnormalities on the vertebral axis in pacu larvae after 30 days of rearing under laboratory conditions. In contrast, the incidence of skeletal abnormalities observed on vertebral centrum in L S could be associated to a possible deficiency or imbalance of some nutrients in the feeding of specimens that have high growing potential under these systems.…”
Section: Discussionsupporting
confidence: 93%